A new species of Crocodile Newt Tylototriton (Caudata: Salamandridae) from Shan State, Myanmar (Burma) - Grismer, L. Lee; Wood, Perry L. Junior; Quah, Evan S. H.; Thura, Myint Kyaw; Espinoza, Robert E.; Grismer, Marta S.; Murdoch, Matthew L.; Lin, Aung (Zootaxa, 2018)
A phylogenetic taxonomic analysis of a monophyletic subgroup of the salamandrid genus Tylototriton revealed that a newly discovered population from Ngar Su Village, 1 km south of Ywangan, Shan State, Myanmar is a new species and most closely related to T. shanorum from approximately 80 km to the west in the vicinity of Taunggyi, Shan State. Tylototriton ngarsuensis sp. nov. differs from other closely related species of Tylototriton on basis of varying combinations of characteristics associated with it shorter head, larger size, rib nodule morphology, and overall drab, very dark, coloration, along with its genetic differentiation. Tylototriton ngarsuensis sp. nov. also appears to breed later in the year than most other species. Unfortunately, this species like many other Asian newts, is being harvested for the pet and medicinal trade and given its restricted distribution, this could pose a serious threat to its long-term survival.